RACIONALIDADE INSTRUMENTAL E EDUCAÇÃO INFANTIL: ANÁLISE CRÍTICA DO SISTEMA DE ENSINO APOSTILADO - BRANCHER, ANGELA T. OLIVEIRA (2024)
This dissertation aimed to critically examine the instrumental rationality inherent in the Apostilado Educational System and its profound impact on the development of a utilitarian subjectivity. The central research inquiry is framed as follows: How does instrumental rationality manifest within the "Letrar" workbook of Group 4, part of the Positivo Educational System? The overarching objective is to explore the nuances, configurations, and implications of instrumental rationality within the realm of Early Childhood Education. Specific goals include deliberating on the formation of reason and the knowledge process in the context of the evolving bourgeois society, grounded in Critical Theory; elucidating key aspects discussed in literature pertaining to Apostilado Teaching Systems in the Brazilian educational landscape, aimed at characterizing the discourse surrounding this subject; examining the intricate relationship between Apostilado Teaching Systems and the commodification of culture; scrutinizing the expression of instrumental rationality in the aforementioned workbook and assessing its alignment with the BNCC (National Curricular Common Base), exploring if the material adheres to the principles outlined in this foundational document. The qualitative methodology adopted adheres to the critical-dialectical approach and is characterized by a bibliographical and documentary framework, drawing insights from the works of Theodor Adorno, Max Horkheimer, and Walter Benjamin—luminaries in the realm of Critical Theory. The findings suggest that workbooks operate within a rationality that diverges from the innate characteristics of childhood, conditioning young learners to adopt attitudes incongruent with their natural childlike tendencies. The workbook activities, marked by coldness, calculability, and mechanization, effectively encircle childhood within conceptual boundaries.